The digital Bay Psalm book : a virtual reconstruction of the new world's first English-language book - Christie-Miller, Ian.; Cattrell, Kevin; Eames, Wilberforce (Tuscaloosa, Ala : University of Alabama Press, 2010)
In 1638, the first printing press was imported to the Massachusetts Bay Colony and a group of local religious leadersincluding, it is thought, Richard Mather, John Cotton, and Richard Eliotset about to create a plain and familiar translation of the psalms and words of David into English metre for use in the colonys church meetings. Earlier psalteries had been brought to the New World by colonists, but in Puritan thought they had strayed too far from the original Hebrew text. In 1640, The Whole Booke of Psalmes Faithfully Translated into English Metre was published in Cambridge; it was the first book published in the American Colonies. The Bay Psalm Book, as it has come to be known, consists of a substantial introduction summarizing the creators philosophy and intentions, followed by translations of the Psalms rendered into meter, enabling them to be sung to well-known tunes of the day. The psaltery was soon in widespread use on both sides of the Atlantic. It went through multiple printings and editions before being succeeded by newer texts in later decades. Generations of theologians and scholars have turned to The Bay Psalm Book, considering it from a variety of perspectives. Besides its significance as a religious treatise, spiritual guide, and historical document, The Bay Psalm Book is also recognized as an important milestone in the evolution of the American musical tradition. In recent years, a new generation of scholars has returned to the book, seeing it from fresh perspectivesas a social document, for example, and as a physical artifact of early American life in the Massachusetts Bay area. The Digital Bay Psalm Book gives scholars, researchers, and enthusiasts alike a rich and intimate experience of the book as it was known by its earliest readers. As an electronic-only publication offered as a downloadable PDF, The Digital Bay Psalm Book takes advantage of digital technology to offer meticulously rendered photographs of the 7.25 x 4 inch book, one of several once owned by Thomas Prince, scholar and minister of Bostons Old South Church from 1718 to 1758. In this format, users are able to zoom in to examine each individual page, the quality of the paper and printing, marginalia, notes, and other marks accrued over the centuries, yielding insights into the owners use and understanding of the text as well as the very life of the book itself. In addition, Christie-Miller provides four supplements that shed light on the technology and craft that went into the creation of Americas first English-language book.
Title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references.
Master record variable field(s) change: 630
Keywords: Bible; Bible. -- Paraphrases, English; Bible; Bible; Psalms (Music); RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Biblical Studies -- Wisdom Literature; Psalms (Music); Multi-User; Electronic books; Paraphrases